Exploring Potential Complement Modulation Strategies for Ischemia–Reperfusion Injury in Kidney Transplantation - Dario Troise; Costanza Allegra; Luciana Antonia Cirolla; Silvia Mercuri; Barbara Infante; Giuseppe Castellano; Giovanni Stallone (Antioxidants)
The complement system plays a crucial role in regulating the inflammatory responses in kidney transplantation, potentially contributing to early decline in kidney function. Ischemia–reperfusion injury (IRI) is among the factors affecting graft outcomes and a primary contributor to delayed graft function. Complement activation, particularly the alternative pathway, participates in the pathogenesis of IRI, involving all kidney compartments. In particular, tubular epithelial cells often acquire a dysfunctional phenotype that can exacerbate complement activation and kidney damage. Currently, complement-modulating drugs are under investigation for the treatment of kidney diseases. Many of these drugs have shown potential therapeutic benefits, but no effective clinical treatments for renal IRI have been identified yet. In this review, we will explore drugs that target complement factors, complement receptors, and regulatory proteins, aiming to highlight their potential value in improving the management of renal IRI.